RADAR CROSS-SECTION IMAGING IN SYNTHETIC APERTURE RADAR WITH LINEAR ANTENNA ARRAY AND ADAPTIVE RECEIVER - Volosyuk, V. K.; Zhyla, S. S.; Ruzhentsev, M. V.; Sobkolov, A. D.; Tserne, E. O.; Kolesnikov, D. V.; Vlasenko, D. S.; Topal, M. S. (Radio Electronics, Computer Science, Control, 2020)
Context. There are a large number of RCS estimation methods in synthetic-aperture radars (SAR), which differ by precision, RCS recovery time of an observation area and complexity of implementation. At the same time, the optimal method, which is a generalization of all existing ones and characterizes both spatial and temporal optimal signal processing, has not been synthesized. Also, usually problem statements do not take into account the stochastic structure of signals reflected from most underlying surfaces. As a result, further ways of improving resolution, optimal SAR structure and maximum achievable precision of estimation of RCS are not determined. Objective. The goal of the work is to solve the problem of synthesis of the optimal method of RCS surfaces restoration as a statistical characteristic of spatially-inhomogeneous random scattering coefficient in aerospace-based radio engineering systems with moving linear antenna arrays and adaptive spatio-temporal signal processing. Method. Applying the method of maximum likelihood estimation and taking into account a priori information about the statistical characteristics of the received spatio-temporal fields a super-resolution method of RCS estimation on spatial coordinates is derived. The generalized problem statement has shown the optimal method of surface observation that allows to overcome the contradiction between the size of the observation area and the accuracy of the parameter estimates. The obtained method allows to achieve highest resolution (as for SpotLight mode) of radar images for wide area of observation (as for Stripmap mode). It is shown that the general algorithm can be adapted to particular solutions with limited statements of the problem. In contrast to the well-known method of aperture synthesis the processing of the received field in the antenna array and receiver is adaptive and depends on the signal-to-noise ratio. Results. The optimal method of area scanning in onboard SAR with antenna arrays and the corresponding method of adaptive spatio-temporal signal processing can be used to describe the receiving path of cognitive on-board radar for remote sensing. Conclusions. The obtained optimal method can be considered as a modified method of aperture synthesis with a multi-beam spotlight mode with the possibility of adaptive radiation pattern formation and signal time processing. In contrast to the classical method performing matched-filtering of the received signal with the reference signal, the modified method additionally decorrelates signals reflected from the earth’s surface. As a result of this decorrelation the characteristic intervals of speckles (the size of the spotted pattern of the image) will be significantly smaller than with match-filtering. Therefore, their subsequent smoothing with the same efficiency can be performed by windows of smaller width. Such processing together with a multi-beam spotlight mode will significantly increase the resolution of the SAR with an expanded area of view.